Aplikasi Photostock Berbasis Mobile - Santoso, Bambang Kurniawan; Gunadi, Kartika; Purbowo, Anita Nathania (Jurnal Infra, 2018)
In this period of time, a photo is a common thing. Photo serves as a medium to store memories of important events around us. Mastering the science of photography requires the skill and techniques so that photographs or works produced will be good enough to be sold. However, the skill and results of good photography lack the container to turn photography as one’s income. The lack of such containers resulted in the photographs being viewed only as works of art. This causes the hobby as a photographer as well as skills in photography sometimes do not gain their economic value.So, a container is needed to facilitate the sale and purchase of photographs produced by photographers or the public. In the Photostock application also has a built-in watermark feature that can automatically add a watermark in your photos in order to avoid copyright infringement. In this application users also can chat with the photo seller.Based on the results of the questionnaire obtained for the application display quality, 60% of other respondents answered not bad and 40% of the other respondents answered well. For feature completeness, 40% of respondents answered not bad, 40% answered well, 20% answered very well. For the entire application, 80% of respondents rated the program as good, and 10% of respondents rated the program very well.